The contemporary endovascular treatment of intracranial aneurysms - Alpay, Kemal (fi=Turun yliopisto|en=University of Turku|, 2022)
The first endovascular treatment of intracranial aneurysms began with simple coiling in 1991. Ever since, it has developed significantly, and endovascular treatment is now the first choice for most intracranial aneurysms. However, some intracranial aneurysms such as wide-necked, blood-blister-like, fusiform and dissecting intracranial aneurysms are not suitable for simple coiling. In 2008, intraluminal flow diversion was introduced for uncoilable saccular intracranial aneurysms of the internal carotid artery, and since then, the indications of intraluminal flow diversion have expanded to complex aneurysms like blister-like, dissecting, and fusiform intracranial aneurysms. In 2010, intrasaccular flow disruption was introduced with the Woven EndoBridge (WEB) for the treatment of naïve wide-necked bifurcation aneurysms. Several studies have shown the safety and efficacy of flow diverters and WEB in the treatment of intracranial aneurysms. In our study the safety and efficacy of the WEB and flow diverters were assessed in Finnish population. Furthermore, we identified and analysed the factors influencing radiological outcomes after the contemporary endovascular treatments. A rate of 90% adequate radiological outcomes can be achieved in the treatment of naïve and recurrent wide-necked intracranial aneurysms with the WEB. No rupture or re-rupture observed after the WEB treatment. The flow diverters can provide a high occlusion rate for elective and acutely ruptured intracranial aneurysms. However, a 45% rate of complications was observed in flow diversion for acutely ruptured intracranial aneurysms. The WEB for wide-necked intracranial aneurysms including wide-necked recurrent intracranial aneurysms appears to be safe and efficient, and is a valuable alternative when the conventional methods are not amenable. The aneurysm morphology and size seem to influence the radiological outcomes after the WEB treatment. Flow diverters provides high occlusion rates. However, the flow diversion of acutely ruptured intracranial aneurysms carries a high rate of complications. Flow diversion can be justified as a last-resort option when other endovascular methods are not suitable for acutely ruptured intracranial aneurysms.

Aivovaltimoaneurysmien nykyaikainen suonensisäinen hoito Aivovaltimoaneurysma hoidettiin koiliembolisaatiolla onnistuneesti ensimmäisen kerran vuonna 1991, ja siitä lähtien endovaskulaariset tekniikat ovat kehittyneet merkittävästi. Endovaskulaarinen menetelmä onkin nykyään ensisijainen valinta useimpien aneurysmien hoitoon. Koska rakkulamaiset, dissekoivat ja fusiformiset aneurysmat ovat vaikeita hoitaa tavanomaisilla endovaskulaarisilla menetelmillä, vaikeahoitoisia aneurysmia varten otettiin vuonna 2008 käyttöön flow diverter -stentit. Niiden alkuperäinen käyttöaihe oli sisemmän kaulavaltimon jättianeurysmien hoito; nyt käyttöaiheet ovat laajentuneet niin rakkulamaisten kuin dissekoivien aneurysmien hoitoon. Intrasakkulaarinen laite Woven Endobridge (WEB) kehitettiin vuonna 2010 leveäkaulaisten aivovaltimoaneurysmien hoitoon. Useat tutkimukset ovat osoittaneet sekä flow diverter -stentin sekä WEB:in turvallisuuden ja tehokkuuden aivoaneurysmien hoidossa. Tutkimuksessa arvioitiin WEB ja flow diverter -hoidon turvallisuutta ja tehokkuutta Suomessa. Erityistä huomiota kiinnitettiin tekijöihin, jotka ennustavat radiologisia tuloksia nykyaikaisen hoidon jälkeen. Tutkimuksella todettiin, että WEB-hoidolla voidaan saavuttaa 90%:sti lähes täydellinen radiologinen hoitotulos. WEB-hoidon jälkeen aneurysmien puhkeamista ei havaittu. Flow diverter -hoidolla saavutetaan 90%:sti täydellinen tai lähes täydellinen radiologinen tulos, mutta 45%:lla potilaista esiintyy jokin flow diverter -hoitoon liittyvä komplikaatio akuutisti puhjenneiden aneurymien hoidossa. WEB on tehokas menetelmä sekä uusien että uusiutuneiden leveäkaulaisten aneurysmien hoidossa. Se on käyttökelpoinen silloin, kun perinteiset menetelmät eivät riitä. Aneurysman muoto ja koko vaikuttavat WEB:in hoitotuloksiin. Flow diverterit mahdollistavat hyvän radiologisen hoitotuloksen akuutisti repeytyneissä aivoaneurysmissa. Niiden flow diverter -hoitoon liittyy kuitenkin huomattavan korkea komplikaatioriski, mutta mikäli muu menetelmä ei potilaan akuutisti puhjenneen aneurysman hoitoon sovellu, sitä voidaan viimeisenä hoitomuotona perustellusti käyttää.